Optimization of Additional Chitosan on Mechanical Properties Edible Film from Avocado Seed Starter - Ikhsani, Anugrah Putri; Dewata, Indang (Jurnal Kependudukan dan Pembangunan Lingkungan, 2022)
Abstract : Edible film is a thin plastic with a thickness of less than 0.25 mm which serves to protect food products. The purpose of this study was to determine the optimum concentration of addition of chitosan to edible film made from avocado seed starch on mechanical properties and to compare the mechanical properties of edible film with the value of Japenese Industrial Standard (JIS) Z1707. This research was conducted by adding 4% polyethylene glycol as a plasticizer and varying the addition of chitosan with a concentration of 0%; 0.5%; 1%; 1.5%; and 2%. The optimum conditions for the addition of chitosan at a concentration of 1%, with a tensile strength value of 1.235 Mpa, an elasticity value of 4.643 Mpa, and an elongation value of 0.266 Mpa. The tensile strength and elasticity values of the edible film have met the Japenese Industrial Standard (JIS) Z1707 but the elongation value has not met because the edible film produced is fragile so it breaks easily and causes the edible film to have a low elongation value. Keywords: Chitosan, Edible film, Avocado seeds